VALIDITY OF SENSOR-BASED, HABITUAL PHYSICAL ACTIVITY AND GAIT ANALYSIS IN MULTIMORBID, OLDER PERSONS. (11th November 2018) - Hauer, K; Bongartz, M; Kiss, R; Lacroix, A; Ullrich, P; Eckert, T; Jansen, C; Mellone, S
Abstract: The aim of the study was to investigate the biometrical quality of a newly developed activity monitor (uSense) to document established physical activity (PA) parameters as well as innovative qualitative and quantitative gait characteristics for habitual activity behavior in multi-morbid, older adults. Validity, test-retest reliability, and feasibility of established (including activity counts, MET-Intensities, number/duration of gait episodes/steps) as well as newly developed gait characteristics, which have not been documented before for habitual assessment (including number, velocity, duration of turnings, various parameters for gait symmetry/ regularity), have been analyzed for multimorbid, geriatric patients with cognitive impairment (n=110) discharged from ward-based rehabilitation. On average, Spearman correlations of established and innovative uSense parameters with clinically relevant parameters were high for motor performances (range for rhos: 0.02 – 0.63) and life space (0.01 – 0.59) and low to moderate for cognitive status (0.01 – 0.25), and age (0.01 – 0.30), indicating moderate to good construct validity. Concurrent validity was high as PA parameters measured by the U-Sense monitor showed consistently high correlation with equivalent parameters measured by another well-established ambulatory motion sensor (PAMSysTM) (0.59 – 0.91). Moderate to excellent test-retest reliability was shown for all uSense parameters (ICC: 0.68–0.97) and good feasibility could be shown, as 85.5% of all measurements were completed without failure. The uSense monitor allows documentation of established and innovative qualitative-quantitative parameters for habitual PA behavior which have so far only been assessed in laboratory settings in multi-morbid, cognitively impaired, older adults with moderate to good validity and high test-retest reliability.